I need help step by step if anyone has time thanks -5(3x + 9 - 7y) Thanks so much
Follow Math Help Forum on Facebook and Google+
What are you trying to find? If its just multiply bracket by -5 then: -5 * 3x = -15x -5 * 9 = -45 -5 * -7y = 35y -15x - 45 + 35y
what do you want to do? expand it? if that is so... -5(3x + 9 - 7y) so what we do is multiply the -5 into 3x, 9 and -7y. Since it literally means -5 * (3x + 9 - 7y) so it will become: -15x - 45 + 35y (-5 x 3x = -15x) (-5 x + 9 = -45) (-5 x -7y = 35y)
Thanks Geometor and r_maths!
-5 (3x + 9 - 7) I am sorry I did not let you know what I was looking for sorry, sorry
Originally Posted by breanna2471 -5 (3x + 9 - 7) I am sorry I did not let you know what I was looking for sorry, sorry u(x)=-5 (3x + 9 - 7)=-5(3x+2) -qbkr21
View Tag Cloud